2010
DOI: 10.1029/2009jc005512
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution climatology of the northeast Atlantic using Data‐Interpolating Variational Analysis (Diva)

Abstract: [1] Numerous climatologies are available at different resolutions and cover various parts of the global ocean. Most of them have a resolution too low to represent suitably regional processes and the methods for their construction are not able to take into account the influence of physical effects (topographic constraints, boundary conditions, advection, etc.). A high-resolution atlas for temperature and salinity is developed for the northeast Atlantic Ocean on 33 depth levels. The originality of this climatolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(111 citation statements)
references
References 55 publications
5
103
0
3
Order By: Relevance
“…Only this section of the AzC presents a seasonal variation of its meridional position (see also Siedler and Finke, 1993). This removes inconsistency between the reported 2 • northward shift of the front of the AzC in winter, obtained from a coarse-resolution study by Stramma and Siedler (1988), and a recently demonstrated stability (within 0.25 • limit) of the AzC axis, integrated over the full length of the current (Lázaro et al, 2013).…”
Section: Seasonal Variability In the Medtrans Climatologymentioning
confidence: 93%
See 2 more Smart Citations
“…Only this section of the AzC presents a seasonal variation of its meridional position (see also Siedler and Finke, 1993). This removes inconsistency between the reported 2 • northward shift of the front of the AzC in winter, obtained from a coarse-resolution study by Stramma and Siedler (1988), and a recently demonstrated stability (within 0.25 • limit) of the AzC axis, integrated over the full length of the current (Lázaro et al, 2013).…”
Section: Seasonal Variability In the Medtrans Climatologymentioning
confidence: 93%
“…2) complements the existing gridding methods (WOA09, WOA13, Schmidtko et al, 2013, Troupin et al, 2010 and the resulting climatic fields provide additional details on temperaturesalinity distributions (described in Sect. 3).…”
Section: Bashmachnikov Et Al: Temperature-salinity Distribution Imentioning
confidence: 99%
See 1 more Smart Citation
“…Static interpolation approaches (e.g., optimal interpolation [Gandin, 1965;Reynolds and Smith, 1994], objective mapping [Wong et al, 2003;Böhme and Send, 2005;Böhme et al, 2008], and Data-Interpolating Variational Analysis [Troupin et al, 2010[Troupin et al, , 2012Korablev, 2014 in addition, exploit modeled physics and provide temporally and spatially varying 4-dimensional analysis fields. The former approaches need a scale representing the mean field, while the latter, in addition, needs spatial and temporal scales representing the anomaly field to fully exploit the information embedded in in-situ data.…”
Section: Resultsmentioning
confidence: 99%
“…The present scale estimates pose a requirement from a basin-scale data assimilation on a sampling strategy. Static interpolation approaches (e.g., optimal interpolation (Gandin, 1965;Reynolds and Smith, 1994), objective mapping (Wong et al, 2003;Böhme and Send, 2005;Böhme et al, 2008), and data-interpolating variational analyses (Troupin et al, 2010(Troupin et al, , 2012Korablev, 2014) exploit statistical information of data to derive a mean analysis field. Data assimilation approaches, in addition, exploit modeled physics and provide temporally and spatially varying fourdimensional analysis fields.…”
Section: Discussionmentioning
confidence: 99%